Pemeliharaan Lightning Arrester (LA) pada Gardu Induk Saketi 150kv di PT. PLN (Persero) ULTG Rangkasbitung - Bagus Dwi cahyono; Shoimatussururoh Shoimatussururoh (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Air transmission lines are very susceptible to lightning strikes resulting in traveling waves that can enter electrical equipment. Surge propagation can cause damage to existing electrical equipment on the transmission line of the substation. One component that has an important role in the substation is the Lightning Arrester (LA) as a protection system from lightning strikes. The purpose of this research is to determine the performance of lightning arresters that are more than 10 years old. Therefore, to ensure the safety of the electric power system from surge voltages and keep the lightning arrester performance reliable, it is necessary to carry out maintenance activities on the lightning arrester. The maintenance carried out is testing Leakage Current Measurement (LCM) and replacing lightning arresters. The research method used is the observation research method in the industrial field with interviews, data collection and analysis and literature study. The results of the LCM test on the old R phase lightning arrester are 112.7 A with a percentage of 86.69% in monitor conditions. So it is necessary to replace the old lightning arresters with new conditions. As for the results of the LCM test on the replacement R phase lightning arrester (new) of 33.4 A with a percentage of 25.69% in good condition.